1991
DOI: 10.1128/jb.173.17.5290-5297.1991
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa alkaline protease: evidence for secretion genes and study of secretion mechanism

Abstract: A 6.5-kb DNA fragment carrying the functions required for specific secretion of the extracellular alkaline protease produced by Pseudomonas aeruginosa was cloned. The whole 6.5-kb DNA fragment was transcribed in one direction and probably carried three genes involved in secretion. The expression in trans of these genes, together with the apr gene, in Escherichia coli allowed synthesis and secretion of the alkaline protease, which was extensively investigated by performing pulse-chase experiments under various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 32 publications
2
50
0
3
Order By: Relevance
“…No appreciable amount of proteolytic or elastolytic activity was detected in toluene cellular extracts, indicating the lack of intracellular accumulation of active enzymes (Table 1). This observation was in agreement with earlier work (11,15,16,18,29,30). Examination of both types of MVs for protease activity demonstrated the association of active enzyme.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…No appreciable amount of proteolytic or elastolytic activity was detected in toluene cellular extracts, indicating the lack of intracellular accumulation of active enzymes (Table 1). This observation was in agreement with earlier work (11,15,16,18,29,30). Examination of both types of MVs for protease activity demonstrated the association of active enzyme.…”
supporting
confidence: 82%
“…In contrast, elastolytic activity was detected exclusively in culture supernatants and was not affected by removal of vesicles from cell-free culture supernatants. Previous studies have demonstrated that the enzyme is secreted as a proenzyme that becomes active only as it is released into the supernatant (15,28). For this Figure 6A and B show gentamicintreated cells labelled for PLC.…”
mentioning
confidence: 99%
“…In each case the protease is secreted via an ABC transporter, often linked to the protease structural gene in the same operon. However, the genetic organization of the protease (prt) operon varies, as does the number of proteases secreted (Ahn et al, 1999;Akatsuka et al, 1995Akatsuka et al, , 1997Duong et al, 1992;Ghigo & Wandersman, 1992a, b;Guzzo et al, 1991b;Kawai et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have cloned the elastase structural gene, lasB (3,7,36) and the alkaline proteinase gene, aprA (1,10,28). There are several reports describing the methods used to determine the concentration of the pathogenic factors produced by P. aeruginosa (2, 4, 5, 13, 16-18, 20, 30, 32).…”
mentioning
confidence: 99%